The right as a structure and as a form: a debate (Società e diritti, 2016)
The text presents the main comments to the theses of Prof. Catelani expressed at the seminarheld at the University of Milan on 28 January 2016 and on the occasion of the meeting of May4, 2016 held in Brixen.Key words: fundamental rights, public administration, legal positivism.